CUISENAIRE LEARNING MEDIA FOR ADDING, SUBTRACTING, MULTIPLYING, AND DIVIDING INTEGERS - Ratni Purwasih; Indah Puspita Sari; Ratna Sariningsih (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This study aims to describe the manufacture and use of Cuisenaire rod learning media for understanding the concepts of addition, subtraction, multiplication, and division of integers for elementary school students. The research method used is literature study, which is a series of activities related to the methods of collecting library data, reading and recording, and processing research materials. This research uses a qualitative approach. Data sources and research results in library research in the form of a description. Data sources are bibliographic or come from various literature, including books, journals, newspapers, personal documents, etc. The research results are that the utilization of Cuisenaire rod media is more optimized on learning in elementary schools, especially in addition, subtraction, multiplication, and division of integers because Cuisenaire rod media can help understand and can concrete the concept of numbers. In addition, it can be used as reference material for research on learning addition, subtraction, multiplication, and division of integers by utilizing different learning media.